2014
DOI: 10.1016/j.electacta.2014.03.140
|View full text |Cite
|
Sign up to set email alerts
|

A potentiometric disposable sensor strip for measuring pH in saliva

Abstract: Abstract.In this paper, the preparation of a potentiometric strip for pH monitoring in saliva samples is reported. The potentiometric strip consists of a solid contact pH-selective and of a solidcontact ionogel reference electrode prepared on a dual screen printed substrate. The screen printing protocols, i.e., type of inks and number of deposits, were adjusted to relatively improve the batch reproducibility and the stability of the pH sensor. The pH of real saliva samples was monitored using the optimised pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 28 publications
1
38
0
1
Order By: Relevance
“…), there is tremendous interest in developing wearable sensors for important chemical markers relevant to health or fitness (Windmiller and Wang, 2013; Matzeu et al, 2015; Bandodkar and Wang 2014). Significant progress has been made recently in developing wearable electrochemical sensors that detect metabolites and electrolytes in sweat, saliva, and tears (Jia et al, 2013; Bandodkar et al, 2013; Bandodkar et al, 2014b; Bandodkar et al, 2015; Kim et al, 2014; Kim et al, 2015; Zuliani et al, 2014; Thomas et al, 2012; Yao et al, 2012). Saliva is a great diagnostic fluid providing an alternative to direct blood analysis via the permeation of blood constituents without any skin-piercing for blood sampling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), there is tremendous interest in developing wearable sensors for important chemical markers relevant to health or fitness (Windmiller and Wang, 2013; Matzeu et al, 2015; Bandodkar and Wang 2014). Significant progress has been made recently in developing wearable electrochemical sensors that detect metabolites and electrolytes in sweat, saliva, and tears (Jia et al, 2013; Bandodkar et al, 2013; Bandodkar et al, 2014b; Bandodkar et al, 2015; Kim et al, 2014; Kim et al, 2015; Zuliani et al, 2014; Thomas et al, 2012; Yao et al, 2012). Saliva is a great diagnostic fluid providing an alternative to direct blood analysis via the permeation of blood constituents without any skin-piercing for blood sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Several efforts have more recently developed salivary sensors based on screen-printing techniques that take advantage of scalable low-cost fabrication. For example, Diamond’s group has developed disposable potentiometric pH sensor strips (Zuliani et al, 2014), and our group has demonstrated a wearable salivary lactate sensor using a mouthguard platform (Kim et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, electrochemical methods are typically straightforward and inherently quantitative, and require simpler operation and setups. Electrochemical methods, however, have downsides, such as long-term instability and vulnerability to electrode fouling, but nevertheless, they are the most commonly used methods for pH detection, whereby the potential (potentiometric) [20,21,[51][52][53][54][55][56], current (amperometric) [57][58][59][60][61][62][63], or charge in an electrochemical cell serve as the analytical signals. Indeed, the glass electrode is currently the most commonly used electrochemical sensor for potentiometric pH measurements.…”
Section: Ph Sensing Mechanismmentioning
confidence: 99%
“…[18][19][20][21] In addition, an array of pH sensors provide a better mapping of tissues or organs than a single-spot device because of possible heterogeneities across different sites and along the depth of the sample. 22,23 In this regard, it is important to note that the fabrication of an array from glass-type pH electrodes is a difficult process.…”
Section: Introductionmentioning
confidence: 99%